Brushless Field Excitation Scheme for Wound Field Synchronous Machines - Syed Sabir Hussain Bukhari; Ghulam Jawad Sirewal; Faheem Akhtar Chachar; Jong-Suk Ro (Applied Sciences, 2020)
A new harmonic field excitation technique for the brushless operation of wound field synchronous machines (WFSMs) is proposed in this paper. The proposed scheme involves conventional three-phase and single-phase inverters operating at different frequencies and supply input current to the armature winding simultaneously. This results in a composite output current of the inverters, which contains fundamental as well as the third harmonic current components. The fundamental is utilized to develop the stator field, on the other hand, the third harmonic is used for developing the pulsating magnetomotive force (MMF) in the airgap. This MMF produces a harmonic current in the harmonic winding of the rotor which is later rectified to inject field current to the rotor field winding. The theoretical analysis of the proposed technique is supported using 2-D finite element analysis (FEA).